"Fuera la Corte Suprema". Breves notas sobre las protestas frente al máximo tribunal - Benente, Mauro (2010)
In the present article a brief description is made of the characteristics\nof social demonstrations during the decade of 1990 and of the hectic days of\nDecember 2001, in order to make an account of the demonstrations organized\nby the Labor Lawyer?s Association before the Supreme Court of Justice. It will\nbe affirmed that the judges of the Supreme Court had developed into important\npolitical or actors in the labour law field due to a series of sentences passed by\nthem during the 90?s